Total body irradiation is a crucial risk factor for developing secondary carcinomas after allogeneic hematopoietic stem cell transplantation in childhood - Keslova, P; Formankova, R; Riha, P; Sramkova, L; Snajderova, M; Malinova, B; Luks, A; Sterba, J; Stary, J; Sedlacek, P (Neoplasma, 2020)
Allogeneic hematopoietic stem cell transplantation (HSCT) has become a standard part of therapy for a variety of malignant and non-malignant disorders. With improved outcomes after HSCT, increasing attention has been drawn to late complications in long-term survivors. The development of secondary malignancies is recognized as one of the most serious complications. We have evaluated data from 426 patients (272 males, 154 females) who underwent allogeneic transplantation at a median age of 7.9 years from 1989 till 2017 and were alive more than one year after transplantation for the occurrence of secondary solid tumors. We have documented the occurrence of secondary solid tumors in 20 patients (4.7%). The median duration of the development of secondary solid cancer from HSCT was 11.7 (range, 5.4-21.5 years). 18 out of 20 patients (90%) had total body irradiation (TBI) 12-14.4 Gy as a part of a conditioning regimen. All but two had transplantation for malignant disease. All patients underwent surgery and/or chemo-radiotherapy. Eighteen are alive, and two died due to the progression of their secondary malignancy. The most frequent solid cancer was thyroid carcinoma (n=9). Cumulative incidence of secondary solid cancer in all groups was 15.2±3.9%, in a group using TBI based regimen 34.7±8.9%, in non-TBI (only chemo) group was 1.5±1.1%. Overall, the cumulative incidence is statistically significantly different between the TBI based and non-TBI (chemo only) group. The incidence and number of complications following allogeneic HSCT in childhood are increasing in time. The early diagnosis of secondary malignancies is one of the key tasks of long-life multidisciplinary post-transplant care.
Keywords: Hematopoietic Stem Cell Transplantation; Risk Factors; Transplantation, Homologous; Child; transplantace hematopoetických kmenových buněk; nádory vyvolané zářením; Humans; lidé; Whole-Body Irradiation; Female; Male; příprava pacienta k transplantaci; Neoplasms, Second Primary; Neoplasms, Radiation-Induced; mužské pohlaví; celotělové ozáření; ženské pohlaví; homologní transplantace; Transplantation Conditioning; dítě; sekundární malignity; rizikové faktory